2018
DOI: 10.12701/yujm.2018.35.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sevoflurane and propofol anesthesia on the incidence of hyperglycemia in patients with type 2 diabetes undergoing lung surgery

Abstract: BackgroundThe type and regimen of anesthesia may affect perioperative hyperglycemia following major surgical stress. This study compared the effects of sevoflurane and propofol on the incidence of hyperglycemia and clinical outcomes in diabetic patients undergoing lung surgery.MethodsThis retrospective study included 176 patients with type 2 diabetes mellitus who had undergone lung surgery. Blood glucose levels and clinical outcomes from the preoperative period to the first 2 post-operative days (PODs) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
3
Order By: Relevance
“…A previous investigation had found that even though mean blood glucose was lesser in propofol group than the sevoflurane group, it did not translate into improved postoperative outcomes and reduced short-term mortality in the propofol group. [ 21 ] Although in the present study the measurement of long-term outcomes was not set up to be the primary outcome, we recorded the time required for the patients to achieve an Aldrete score of 9 which signified the readiness of shifting the patient from PACU. Significant differences were observed in patients of the propofol group to achieve the same Aldrete score compared to the sevoflurane and desflurane groups, although these differences might not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation had found that even though mean blood glucose was lesser in propofol group than the sevoflurane group, it did not translate into improved postoperative outcomes and reduced short-term mortality in the propofol group. [ 21 ] Although in the present study the measurement of long-term outcomes was not set up to be the primary outcome, we recorded the time required for the patients to achieve an Aldrete score of 9 which signified the readiness of shifting the patient from PACU. Significant differences were observed in patients of the propofol group to achieve the same Aldrete score compared to the sevoflurane and desflurane groups, although these differences might not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers attributed the increase after surgery to the short half-time of propofol-sufentanil and also to an increase in the glucagon/insulin ratio. Kim et al (30) reported that the patients with type 2 diabetes who underwent pulmonary surgery were present with perioperative hyperglycemia, though they did not detect a difference in the incidence of sevoflurane and propofol anesthesia during the operation, and that it was, however, significantly lower in the propofol group at 2nd postoperative hours. The researchers attributed this to opioid used at higher doses during propofol anesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…Bazı klinik çalışmalarda, DM olmayan hastalarda cerrahi süresince propofol anestezisinin volatil anesteziklere kıyasla daha düşük kan şekeri seviyelerine yol açtığı (34,35) ; Kitamura ve ark. (35) propofolün, farklı tipte ameliyat geçiren DM olmayan hastalarda ameliyat sırasında sevoflurandan daha düşük kan şekeri seviyelerini tetiklediği; major torasik cerrahi geçiren 188 Tip 2 DM hastasının değerlendirildiği retrospektif bir çalışmada ise, sevofluran veya propofol kullanılarak yapılan anestezinin perioperatif dönemde benzer bir hiperglisemi sıklığıyla sonuçlandığı gösterilmiştir (36) . Yüksek doz opioid kullanımının hipotalamik-hipofiz eksenini ve sempatik sinir sistemi aktivasyonunu baskılayarak cerrahiye hiperglisemik yanıtı ortadan kaldırdığı bildirilmiştir (37) .…”
Section: İntraoperatif Dönemunclassified